A Communication Protocol for Fog Computing Based on Network Coding Applied to Wireless Sensors - Marques, Bruno; Machado, Igor; Sena, Alexandre; Castro, Maria Clicia (2017 International Symposium on Computer Architecture and High Performance Computing Workshops (SBAC-PADW), 2017)
A communication protocol for fog computing should be efficient, lightweight and customizable. In this work we focus in a communication protocol for fog nodes composed of wireless sensors, which are spatially distributed autonomous sensors monitoring physical or environmental conditions. Problems with data congestion and limited physical resources are common in these networks. For the optimization of data flow, it is important to apply techniques that reduce the transmitted data. We use the network coding technique to demonstrate through experiments the degree of efficiency of data transmission optimization protocols. The experiments were performed through a wireless sensors programming framework composed of TinyOS operating system, NesC programming language and TOSSIM simulator. In addition, we use the Python programming language to simulate the wireless sensor network topology. The results obtained demonstrate a better performance (50% up to 60%) when the network coding technique is applied to the data communication protocol.